Pengaruh Sektor Pariwisata Terhadap Pertmbuhan Ekonomi Di Provinsi Bali Periode 2017-2021 - Rifki Khoirudin; Retno Kumalasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT Being one of the developing countries in Southeast Asia, Indonesia has an economy that is still unstable among countries. The government is trying to make new innovations in industry, agriculture, fisheries and tourism to increase economic development. The province of Bali is one of the provinces with the lowest economic growth in 2020. This can occur due to the presence of Covid-19 which is located almost all over the world. The research aims to determine the influence of the tourism sector on economic growth in the Province of Bali for the 2017-2021 period. The data used in this study is secondary data obtained from the official website of the Central Bureau of Statistics. The data includes panel data which is a combination of time series data and cross section data. Fixed Effect is a suitable model. In this study, the variables used in this study were hotels, restaurants, travel service bureaus and tourist visits. The results show that the hotel variables, travel service bureaus and tourist visits have a significant positive effect and the restaurant variables have a negative and insignificant effect on economic growth in the Province of Bali for the 2017-2021 period. Keywords: Economic Growth, Hotels, Restaurants, Travel Service Agencies, Tourist Visits, Province of Bali